2013
DOI: 10.1136/jnnp-2012-303645
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment after lacunar stroke: systematic review and meta-analysis of incidence, prevalence and comparison with other stroke subtypes

Abstract: BackgroundCognitive impairment and dementia are common after stroke. It is unclear if risk differs between ischaemic stroke subtypes. Lacunar strokes might be less likely to affect cognition than more severe, larger cortical strokes, except that lacunar strokes are associated with cerebral small vessel disease (SVD), which is the commonest vascular cause of dementia.MethodsWe searched MEDLINE and PsychINFO for studies of mild cognitive impairment (MCI) or dementia after lacunar or cortical ischaemic stroke. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(182 citation statements)
references
References 40 publications
7
162
1
4
Order By: Relevance
“…Chronic lacunar infarcts, even silent, has been associated with subtle cognitive deficits, 20 increased risk of future dementia, 21 and poststroke cognitive decline. 22 However, in our study we failed to find an association between previous lacunar stroke and worse cognitive performance, possibly because a small number (19%) of our patients had subclinical lacunar infarcts predating their event. Nor was WMH volume associated with worse cognitive performance in our group.…”
Section: Discussioncontrasting
confidence: 46%
“…Chronic lacunar infarcts, even silent, has been associated with subtle cognitive deficits, 20 increased risk of future dementia, 21 and poststroke cognitive decline. 22 However, in our study we failed to find an association between previous lacunar stroke and worse cognitive performance, possibly because a small number (19%) of our patients had subclinical lacunar infarcts predating their event. Nor was WMH volume associated with worse cognitive performance in our group.…”
Section: Discussioncontrasting
confidence: 46%
“…A recent review by Makin et al 34 on cognitive impairment after lacunar stroke showed that approximately 30% of patients develop cognitive impairment in the 4 years following a lacunar stroke, a proportion that is comparable to nonlacunar stroke. Accordingly, in the LADIS, 35 the number of new lacunes during a 3-year follow-up was related to progressive cognitive impairment, which was apparent as a decline in executive functions, as well as in speed and motor control.…”
Section: The Prevalence Of Pscimentioning
confidence: 99%
“…2 However, while severe stroke increases cognitive impairment after stroke, prediction of post-stroke cognitive impairment in general remains suboptimal, particularly in patients with less severe stroke subtypes such as lacunar stroke, which is surprising since these strokes are typically small, located in subcortical tissues and the clinical features do not include higher cortical dysfunction. 3 In a previous systematic review focusing on lacunar versus non-lacunar ischaemic stroke, it was unclear whether there were differences between stroke subtypes, there were few studies that assessed cognitive impairment at later times (a year or more) after stroke, and little data on factors that predicted cognitive impairment after stroke. 3 Cognitive decline in the years prior to stroke is a well-established risk factor for post-stroke cognitive impairment and dementia.…”
Section: Introductionmentioning
confidence: 99%